1992
DOI: 10.1159/000292748
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Aspirin in Primigravidae with Positive Roll-Over Test

Abstract: In a prospective, randomized, double-blind study for the prevention of pregnancy-induced hypertension and preeclampsia, 41 primigravidae with positive roll-over test (28th-32nd week of pregnancy) received 80 mg aspirin/day or placebo until the end of the 37th week. In the patients treated with acetylsal-icylic acid (n = 22), 3 cases of proteinuria occurred, but no hypertensive pregnancy complication. In the placebo group (n = 19), 10 patients developed pregnancy-induced hypertension (6 of them preeclampsia). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…PND was reported in 21 studies. Regardless of the dose used, LDA started after 16 weeks' gestation had no effect on the risk of PND (RR, 0.90; 95% CI, 0.78–1.03; P = 0.12).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…PND was reported in 21 studies. Regardless of the dose used, LDA started after 16 weeks' gestation had no effect on the risk of PND (RR, 0.90; 95% CI, 0.78–1.03; P = 0.12).…”
Section: Resultsmentioning
confidence: 95%
“…Following review of the abstracts, 119 potentially suitable trials were selected for full review. Of these, 40 studies involving 34 807 participants, met the inclusion criteria and were included in the final analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 8377 citations from which we identified 1104 potentially eligible studies that were completely reviewed (Figure ). The inclusion criteria were met by 66 studies, but only 42 of those were included (27 222 women randomized) in the final analysis because several studies recruited over a range of gestational age overlapping 16 weeks. Studies included nulliparous women or women identified at high risk for pre‐eclampsia based on medical history and/or ultrasonographic findings (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 studies reported perinatal mortality [1,4,15,17,27,29,31,33,35,36,39,41-43] (Table 1). The effect of aspirin alone showed no significant effect on risk of stillbirths (RR= 1.15; 95% CI: 0.88 to 1.49) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%